Determinants of Corporate Sukuk Credit Spreads in Indonesia’s Primary Market - Erika Viola; Agus Saur Utomo; Ishak Ishak (Journal of Economics and Management Scienties, 2026)
This study aims to examine the effects of leverage (Debt-to-Equity Ratio/DER), profitability (Return on Assets/ROA), rating, and the book-to-market ratio on the credit spread of corporate sukuk in the Indonesian primary market. The sample consists of 39 corporate sukuk and 10 sovereign sukuk issued through initial public offerings (IPOs) in the primary market and listed on the Indonesia Stock Exchange (IDX) during the 2018–2022 period, selected using purposive sampling. Data were obtained from the Indonesia Bond Market Directory and companies' financial statements published by the Indonesia Stock Exchange. Data were analyzed using multiple linear regression with EViews 12 software. The results indicate that, individually, leverage and profitability do not have a significant effect on corporate sukuk credit spreads. In contrast, sukuk ratings have a significant negative effect, while the book-to-market ratio has a significant positive effect on credit spreads. These findings suggest that sukuk ratings and the book-to-market ratio are important determinants of corporate sukuk credit spreads, whereas leverage and profitability have not been shown to exert a significant influence.